Different perspectives on changes and conflict in the transatlantic world - Costa, C.M.; Fretes Carreras, Luis A. (Portuguese Journal of Social Science, 2018)
The panel 'Transatlantic changes within economic crisis and global conflicts' was presented in the international relations topic area at the CEISAL Congress in Salamanca in 2016. From this panel, we decided to select the presentations that represented a broader perspective of Atlantic relations, covering international relations, economics and literature. This selection gave origin to this special issue to rethink the exchanges during our debate. The articles included embody an approach to contemporary challenges in this area of the world, contributing to the emerging literature on transatlantic relations. We intend to contribute to an interdisciplinary perception of transatlantic relations, and by focusing on relations between Latin America and the other side of the Atlantic, including Europe and the Middle East, we will move the traditional standpoint based on US/Europe relations.